Regional Integration and International Trade in the Context of EU Eastward Enlargement - Tiiu Paas (Hamburg Institute of International Economics (HWWA), 2003)
The paper aims to explore international trade flows of the countries involved in the EU eastward enlargement processes – the current EU members (EU15) and the candidate countries (CC12). The empirical results of the study allow us to conclude that the behaviour of bilateral trade flows within the countries involved in EU eastward enlargement accords to the normal rules of gravitation, having statistically significant spatial biases caused by the trade relations, between the Baltic Sea Region (BSR) countries (the BSR bias), the border countries (the border bias) and the EU member and candidate countries (the East-West bias). The East-West trade relations are still rather weakly developed and there is a statistically significant difference in international trade patterns between the two groups – the current EU members and the applicant countries. The lessons of the Baltic Sea Region in integrating countries with different economic and political backgrounds and developing bilateral trade relations are valuable in supporting EU eastward enlargement and the reintegration of new member countries into Europe.
Keywords: F15; R15; C5; 330; EU enlargement; the Baltic Sea Region; integration; international trade; gravity models; Internationale Wirtschaftsbeziehungen; Handelsregionalisierung; Bias; Gravitationsmodell; Schätzung; EU-Erweiterung; EU-Staaten; Osteuropa; Ostsee